2010
DOI: 10.1111/j.1365-2656.2009.01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of density and temperature on body size in multiple populations of Chinook salmon

Abstract: Summary1. The size individuals attain reflects complex interactions between food availability and quality, environmental conditions and ecological interactions. A statistical interaction between temperature and the density of conspecifics is expected to arise from various ecological dynamics, including bioenergetic constraints, if population density affects mean consumption rate or activity level. Density effects on behaviour or size-selective predation could also generate this pattern. This interaction plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 39 publications
4
111
1
Order By: Relevance
“…Whereas we did not find any conclusive effects of temperature and density interactions on juvenile steelhead growth rates, Crozier et al (2010) found that the negative effects of density on individual Chinook salmon (O. tshawytscha) size were exacerbated at high temperatures, and that growth correlated positively to temperature at relatively low densities. Parra et al (2012) reported on a positive relationship between temperature and size early in ontogeny, and that density-dependent effects posed more important constraints on the size of larger brown trout.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Whereas we did not find any conclusive effects of temperature and density interactions on juvenile steelhead growth rates, Crozier et al (2010) found that the negative effects of density on individual Chinook salmon (O. tshawytscha) size were exacerbated at high temperatures, and that growth correlated positively to temperature at relatively low densities. Parra et al (2012) reported on a positive relationship between temperature and size early in ontogeny, and that density-dependent effects posed more important constraints on the size of larger brown trout.…”
Section: Discussioncontrasting
confidence: 99%
“…The interacting effects of density and temperature have been studied in several recent works (Crozier et al 2010, Parra et al 2012, Baerum et al 2013, and reveal complex constraints on individual growth and size-at-age. Whereas we did not find any conclusive effects of temperature and density interactions on juvenile steelhead growth rates, Crozier et al (2010) found that the negative effects of density on individual Chinook salmon (O. tshawytscha) size were exacerbated at high temperatures, and that growth correlated positively to temperature at relatively low densities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Caspian terns (Hydroprogne caspia) on migrating juvenile salmon (63)(64)(65)(66), impacts of nonnative mysids and lake trout on kokanee and native salmonids in lakes (28,67), complex species interactions (68), and stage-specific growth and survival of some juvenile salmon populations during freshwater and early marine rearing (69,70). General statistical and population models have been used to explore density dependence and carrying capacities in lakeand stream-rearing populations (71)(72)(73)(74). More broadly, trophic modeling has greatly improved the understanding of lake conditions in North America (20,26).…”
Section: Incorporating a Food Web Perspective Into Managementmentioning
confidence: 99%